Universiti Sains Malaysia and looking to Malaysian tradition for guidance. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2010)
Higher educational reform in Malaysia is ultimately engaged with the question of developing creativity in learning and maintaining values in a changing and dynamic world. The approach of Universiti Sains Malaysia to its APEX agenda is an approach tries to couple and develop these two important aims. The argument which is set out in the following discussion is that two seminal Malaysian thinkers provide us with a balanced path and interesting insights into how we can think through advancing these aims.